2007
DOI: 10.15258/sst.2007.35.1.13
|View full text |Cite
|
Sign up to set email alerts
|

High viability recorded in ultra-dry seeds of 37 species of Brassicaceae after almost 40 years of storage

Abstract: Final germination percentages of 25 accessions of Brassicaceae from the UPM (Universidad Politécnica de Madrid) seed bank were evaluated after 38-40 years of storage. The seeds were preserved at temperatures between-5°C and-10°C in flame sealed vials containing dehydrated (blue) silica gel. Seed moisture content ranged between 0.3 and 3% (f.w.b) after storage. Most accessions (ten out of twelve) with high initial (before storage) germination rate (low initial dormancy) maintained these high values almost intac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 18 publications
3
46
0
9
Order By: Relevance
“…Gonzáles-Benito e Perez-Garcia (2001) também não verificaram diferenças entre a germinação de sementes de girassol criopreservadas com teores de água de 6,2 a 8,9% e sementes controle. Uma das vantagens da secagem em sílica é proporcionar um ambiente asséptico, reduzindo a porcentagem de sementes infectadas (Pérez-Garcia et al, 2007) e, embora não tenha sido objetivo desse trabalho, plântulas mais sadias foram obtidas de sementes secadas em sílica, comparadas com a secagem em câmara.…”
Section: Tabela 5 Valores Médios De Plântulas Normais (%)unclassified
“…Gonzáles-Benito e Perez-Garcia (2001) também não verificaram diferenças entre a germinação de sementes de girassol criopreservadas com teores de água de 6,2 a 8,9% e sementes controle. Uma das vantagens da secagem em sílica é proporcionar um ambiente asséptico, reduzindo a porcentagem de sementes infectadas (Pérez-Garcia et al, 2007) e, embora não tenha sido objetivo desse trabalho, plântulas mais sadias foram obtidas de sementes secadas em sílica, comparadas com a secagem em câmara.…”
Section: Tabela 5 Valores Médios De Plântulas Normais (%)unclassified
“…De forma geral, as condições de armazenamento sob baixas temperaturas em sementes com teor de água reduzido podem promover a superação de dormência, há alguns exemplos na literatura que mostram que estas mesmas condições apresentam efeito oposto, ou seja, induzem dormência (Ruiz et al, 1999;Wood et al, 2000;Albrecht e Mccarthy, 2007;Pérez-García et al, 2007). Na presente pesquisa, a desidratação por si só não se mostrou como fator indutor da dormência, pois não foi detectada diferença significativa entre as porcentagens de germinação de sementes com diferentes teores de água, compreendidos entre 16,9% e 4,7%.…”
Section: Resultsunclassified
“…Jones et al (1998) Assim, a dormência de sementes de P. setacea submetidas à conservação em longo prazo é uma ocorrência relevante, que deve ser considerada no estabelecimento de estratégias para a conservação de sementes em bancos de germoplasma. Assim, uma vez que a ocorrência de dormência e sua profundidade podem ser alteradas em condições de conservação em longo prazo (Ellis et al, 1993;Pérez-García et al, 2007), no caso de espécies não domesticadas e até mesmo para algumas cultivadas, é recomendável a utilização conjunta de testes de germinação e de viabilidade (TZ), de forma a permitir a obtenção de melhores estimativas sobre o desempenho de sementes conservadas.…”
Section: Tabela 2 Porcentagem De Germinação (Pg) E Viabilidade (V) Dunclassified
“…Seed dormancy may also be high in wild species and advice on breaking dormancy and promoting the germination of diverse species in genebank monitoring tests has been provided (Ellis et al 1985a, b). Nonetheless, published information on procedures to break dormancy and suitable environments to promote the germination of dormant and non-dormant seed remain limited (Hay and Probert 2013), and dormancy is a particular problem for genebanks holding wild species (Pérez-García et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Several have reported results from several decades monitoring accessions in medium-and/or long-term stores. Those reports have shown evidence of: considerable variation in seed longevity amongst contrasting species in medium-long-term stores (Walters et al 2005); variation amongst species with considerable loss in viability for some in medium-term stores (Lee et al 2013); benefit to seed survival in long-compared with medium-term stores (Agacka et al 2014), or shown this often but not consistently so (Hay et al 2013(Hay et al , 2015; considerable variation in seed survival amongst accessions within a species (Hay et al 2013(Hay et al , 2015; excellent seed survival after 40 years at the recommended long-term seed store conditions (Pérez-García et al 2007) and hence survival periods could not be quantified.…”
Section: Introductionmentioning
confidence: 99%